2015
DOI: 10.1016/j.jpainsymman.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Depression, Fatigue, and Sleep Disturbances as a Symptom Cluster in Women With Breast Cancer

Abstract: Context Depression, fatigue, and sleep disturbances have been identified as a symptom cluster among breast cancer patients. However, few longitudinal studies have examined the temporal relations between these symptoms surrounding diagnosis and treatment. Objectives The current study investigated the co-occurrence of and interrelations between non-somatic depressive symptoms, fatigue, and sleep disturbances in breast cancer patients at three time points: prior to, after, and six to eight months following adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 39 publications
11
98
0
8
Order By: Relevance
“…In addition, in a recent meta-analysis that evaluated the effects of doublet versus single cytotoxic agent treatment for non-small cell lung cancer (47), no between group differences in fatigue occurrence rates were found. Finally, fatigue, feeling drowsy, and sleep disturbance were reported in previous studies to be part of a symptom cluster (48,49). Given that all three symptoms had higher occurrence rates in the patients who received only CTX suggests that when these three symptoms do occur they may interact with each other and result in a higher symptom burden.…”
Section: Symptom Occurrencementioning
confidence: 65%
“…In addition, in a recent meta-analysis that evaluated the effects of doublet versus single cytotoxic agent treatment for non-small cell lung cancer (47), no between group differences in fatigue occurrence rates were found. Finally, fatigue, feeling drowsy, and sleep disturbance were reported in previous studies to be part of a symptom cluster (48,49). Given that all three symptoms had higher occurrence rates in the patients who received only CTX suggests that when these three symptoms do occur they may interact with each other and result in a higher symptom burden.…”
Section: Symptom Occurrencementioning
confidence: 65%
“…In fact, a growing number of recent studies support that fatigue may co-occur with depression and sleep disturbances as part of a symptom cluster in breast cancer patients [30][31][32][33]. Berger et al examined patterns of circadian rhythms and their relationship with fatigue, anxiety, and depression and concluded that disrupted patterns of circadian rhythms were associated with distressing fatigue and depressive symptoms during chemotherapy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Berger et al examined patterns of circadian rhythms and their relationship with fatigue, anxiety, and depression and concluded that disrupted patterns of circadian rhythms were associated with distressing fatigue and depressive symptoms during chemotherapy [30]. Ho et al investigated the co-occurrence of and interrelations between the three symptoms prior to, after and 6 to 8 months following adjuvant chemotherapy, and their findings revealed moderate to large bivariate associations between symptoms, prior to and following treatment [31]. Bower et al examined the impact of fatigue on various components of health-related quality of life in a sample of breast cancer survivors 1 to 5 years after initial cancer diagnosis and concluded that more severe fatigue was associated with significantly higher levels of depression and sleep disturbance [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological distress is prevalently related to fear of recurrence, uncertainty about the future, the ability to live with loss, changes in body image and sense of abandonment by the medical team (10). Physical symptoms are also a constant concern for breast cancer (BC) survivors including: fatigue (11); pain (12); sleep disorders (13); lymphedema (14); menopause (15)(16)(17), fertility concerns (18) and weight gain (19). Consequently, the ability to effectively intervene on psychosocial aspects associated not only with diagnosis of cancer and its treatment, but also with survival is a major challenge (20).…”
Section: Introductionmentioning
confidence: 99%